The generation of wealth in the restaurants establishments located in the regions of Arequipa, Cusco, Lambayeque and La Libertad, year 2013 and the contribution to the regional gross domestic product - Málaga Núñez-Zeballos, Alejandro (2017)
Describes the research carried out by the Observatory Tourist of Peru of the Professional School of Tourism and Hospitality of the University of San Martin de Porres, who poses as an aim to see the generation of the gross domestic product (GDP) of the establishments of restoration in the regions of Arequipa, Cusco, Lambayeque and La Libertad; as well as its contribution to the GDP of each region. The methodology used was exploratory, transverse, descriptive and hermeneutic. We gave a quantitative approach, where we applied techniques of accounting and economic research of the satellite accounts. The documentary and technical field technique were used. The universe was made up of 100 % of establishments in the restoration of the regions of Arequipa, Cusco, Lambayeque and La Libertad. The surveys were applied to executives and heads of establishments.